Challenges in Developing Curriculum Training for Enhancing the Competencies in the 21st Century Skills-Based Learning in the New Normal Situations - VATHANAVONG, Thongthiane; KURUDA, Ariyabhorn; VATHANAVONG, Phaivanh; SEMHIRUN, Kritsana; ASAI, Kilaysone (Souphanouvong University Journal Multidisciplinary Research and Development, 2021)
The objectives of this study were: 1) conduct a needs assessment for training to improve competencies in 21st century competency-based learning in the new normal situations for instructors at Souphanouvong University; 2) develop training curricula to improve 21st century competency-based learning; and 3) evaluate the effectiveness of 21st century competency-based learning as follows: trainee performance, ability to design lesson plans, and trainee satisfaction. The training curriculum development process was conducted in three steps, including baseline data investigation, training curriculum design, training curriculum implementation, and training curriculum improvement. The sample of the study included 167 lecturers and 327 students from 6 faculties of Souphanouvong University in academic years 2020-2021, who were selected by stratified random sampling. Mixed methods were used as the research methodology; an embedded design was developed by exploring quantitative methods and supplementing them with qualitative methods. The research instruments used for data collection were questionnaire and structured interviews. The statistics used included percentage, mean ( ), standard deviation (S.D) and Priority Needs Index Modified (PNIModified). The dependent samples t-test or paired samples t-test was used. The research findings were as follows: A needs assessment to promote 21st century skills based learning in the new normal situations, was at a high level. Developed curriculum training is consistency and suitability can be used in training. The effectiveness of curriculum training was like: Performance after training was higher than before training at .05 level with statistical significance, trainees ability to design lesson plans was at a good level; and trainees' satisfaction with training was at a very good level.